The interaction between a positive muon and multiple quadrupolar nuclei - Bentley, NP; Blundell, SJ (IOP Publishing, 2023)
A positively charged muon implanted in copper sits at an octahedral interstitial site and experiences a magnetic dipolar coupling with six nearest-neighbour quadrupolar I = 3/2 copper nuclei. The resulting avoided level crossing resonance observed as a function of magnetic field provides a means of studying these interactions and understanding the effect of the electric-field gradient due to the muon acting on the quadrupolar nuclei. The effect is usually modelled by considering the interaction between the positive muon and a single copper nucleus, but the other five copper nuclei are equally important. By solving the problem in the full 2(2I + 1)6 = 8192-dimensional Hilbert space, we demonstrate the effect of these additional interactions.